Marketing strategy at UD. Setya Jati Furniture uses SWOT and AHP methods to increase sales volume - Virdyansyah Nayuandika; Siti Rahayu; Hasyrani Windyatri (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2025)
UD. Setya Jati Furniture has undergone a significant transformation from a small wooden decoration store into a business unit specializing in furniture sales. However, the company experienced a decline in sales during the COVID-19 pandemic due to government-imposed lockdowns and public activity restrictions (PPKM). Additional contributing factors included limited promotional activities, incomplete product catalogs, and inefficient order processing. Furthermore, the company had not previously implemented a business development strategy focused on increasing sales volume. To address these issues, this study employed SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis in conjunction with the Analytic Hierarchy Process (AHP) to identify and prioritize effective marketing strategies. The SWOT analysis revealed that UD. Setya Jati Furniture is positioned in quadrant I, indicating strong potential for growth. Based on this position, several strategic recommendations were proposed: maintaining product and service quality, enhancing product differentiation, securing additional capital through low-interest bank loans, expanding to new locations, increasing online promotional efforts, developing a comprehensive price catalog with product utility information, fostering customer loyalty, evaluating inventory levels to manage market fluctuations, optimizing pricing strategies, and innovating product designs in line with industry trends. Among these, the AHP results identified “increasing sales through online promotion” as the highest-priority strategy, with a score of 0.157. The implementation of these strategies is expected to help UD. Setya Jati Furniture sustains its operations and achieves further growth in the competitive furniture industry.